Big Nate : game on! - Peirce, Lincoln (Big Nate, 2013)
"To sixth-grader Nate Wright, life is one big game. So when he suits up for any sport, he does it with an unmistakable swagger. From fine-tuning his trash-talking skills on the basketball court to his cocky 'tude in the soccer goal, Nate can be a bigger challenge to his teammates than their opponents"--Page 4 of cover.